Factors Affecting Small Scale Home-Based Business Performance: A Literature Review - Idris, Zainab (International Journal of Marketing Research Innovation, 2017)
Business performance is paramount for businesses to grow, develop, expand and diversify. Lots of business fails at early stage due to so many factors. The study paper identify factors influencing home- based business performance using secondary source and came up with factors like owner’s gender, sources of finance, information and communication technology, age of business, managerial know- how, customer, and innovation  plays a significant role in the performance of small business in which home based is one. The paper recommends that home- based business have great potential of becoming large businesses if properly managed and will contribute towards economic development. Also the paper will contribute to the field of entrepreneurship as related to the growth and development of home-based businesses. The paper suggests that future studies should apply empirical analysis to further verify the study variables relationships.